Is ghrelin a natural anti-microbial egent? - Aydin, Suleyman; Geckil, Hikmet; Kılıç, Nermın; Erman, Fazilet; Kılıç, Süleyman Sırrı; Yesilada, Ozfer (My University, 2008)
-
Keywords: Ghrelin; Body Weight; Anti-Infective Agents; Peptide Hormones